The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.4025/actascianimsci.v30i2.4710
|View full text |Cite
|
Sign up to set email alerts
|

Diversidade genética de três estoques de piapara (<em>Leporinus elongatus</em>), utilizando RAPD

Abstract: RESUMO. Recentemente a produção aquícola brasileira tem apresentado grande progresso. Dentre as espécies nativas cultivadas no Brasil, a piapara (Leporinus elongatus) tem sido amplamente preconizada. Com objetivo de avaliar os programas de repovoamento, foram analisadas a variabilidade e a divergência genética de três estoques de piapara com a técnica de RAPD (Random Amplified Polymorphic ABSTRACT. Genetic diversity of three stocks of piapara (Leporinus elongatus), using RAPD. Latelly, aquiculture production i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
1
1
0
1
Order By: Relevance
“…High variability in broodstocks presupposes that offspring for restocking also have high variability, making feasible their release in the rivers Paraná and Paranapanema without jeopardizing the natural populations. In broodstock samplings from the same fish pond in Salto Grande for the species P. mesopotamicus and L. elongatus, Povh et al (2008a) and Gomes et al (2008) reported rates (SI = 0.289 and %FP = 56.36%; SI = 0.447 and %FP = 88.8%, respectively) similar to those in current research for PacSG and PiaSG. The above reveals good reproduction management of broodstocks and their viability in restocking programs.…”
Section: Resultssupporting
confidence: 73%
“…High variability in broodstocks presupposes that offspring for restocking also have high variability, making feasible their release in the rivers Paraná and Paranapanema without jeopardizing the natural populations. In broodstock samplings from the same fish pond in Salto Grande for the species P. mesopotamicus and L. elongatus, Povh et al (2008a) and Gomes et al (2008) reported rates (SI = 0.289 and %FP = 56.36%; SI = 0.447 and %FP = 88.8%, respectively) similar to those in current research for PacSG and PiaSG. The above reveals good reproduction management of broodstocks and their viability in restocking programs.…”
Section: Resultssupporting
confidence: 73%
“…2) Entre os fatores que contribuem para a diminuição da variabilidade genética, destacamse a endogamia (Melo et al, 2006;Moreira et al, 2007), a reprodução de um pequeno número de reprodutores e a seleção não intencional, a qual se caracteriza pela seleção de reprodutores com base em uma determinada característica, sem pretensões de melhoramento genético como, por exemplo, de peixes maiores ou menores, e pela não utilização de todo o período reprodutivo (Povh et al, 2008a). Esses fatores são responsáveis pela diminuição da variabilidade genética de estoques de reprodutores (Wasko et al, 2004;Barroso et al, 2005;Povh et al, 2005) e de peixes jovens destinados à soltura no ambiente (Sekino et al, 2002;Gomes et al, 2008;Ortega-Villaizán Romo et al, 2006).…”
Section: Resultsunclassified
“…This is mainly due to the lack of specific primers. Consequently, several researchers used sequenced primers of other species, or rather heterologous primers (OLIVEIRA et al, 2006;RAMOS et al, 2012) or other molecular markers (GOMES et al, 2008;LOPERA-BARRERO et al, 2008aRAMOS et al, 2012). Studies that identify and characterize more primers for the two species are required.…”
Section: Simplementioning
confidence: 99%